(untitled) (Research, Society and Development, 2021)
Objective: To verify whether there is an association between functional capacity and functional health literacy among older adults assisted by the Family Health Strategy. Method: Exploratory descriptive study with a cross-sectional quantitative approach, carried out in the coverage area of ten Family Health Strategy teams, with a total of 350 older adults. Data was collected through a socio-demographic questionnaire and the application of validated instruments to measure functional capacity and functional health literacy. Data was collected from July to December 2017. Descriptive statistical analysis and chi-square, ANOVA and Spearman correlation tests were performed. Results: There was no relationship between basic activities of daily living and functional health literacy. There was a positive correlation between the scores on the scales of instrumental activities of daily living and functional health literacy. Conclusion: There is an association between functional capacity and functional health literacy regarding instrumental activities of daily living.